Expectations and roles of today’s municipal managers: A content analysis of the requirements and management roles of municipal managers in job advertisements - Köpman, Jenni (My University, 2017)
Municipalities have undergone remarkable changes in recent years. Along with these changes, the post and role of municipal manager has changed. This thesis investigates the requirements and qualifications of today’s municipal managers. Furthermore, this thesis studies what kind of management roles municipal managers are expected to perform. The theoretical framework of this study consists of management and management roles, recruitment process as well as municipality and the post of municipal manager. The concept of management as well as functions of leadership and management are explained accordingly to Fayol’s theories. The theory of management roles will be explained according to Mintzberg. Human resource management in the public sector in Finland as well as recruitment will be explained according to Viitala and other scientists. Furthermore, Finnish municipality system, municipality’s bodies and functions are explained as well as the post of municipal manager, especially from the point of view of legislation. The method of this study is qualitative content analysis. The research data consists of 40 job advertisements of municipal managers gathered in 2015–2016 and two recently published research on municipal managers. The 40 job advertisements will be analysed according to Minztberg’s management roles. Municipalities’ demands for today’s municipal managers are high and requirements set for municipal managers are versatile. In a nutshell, municipalities are looking for a co-operative multi-talent with large networks. Previous work experience in several areas is one of the most essential requirement. Especially knowledge of municipal administration and industry are highlighted. Likewise, previous management experience and experience in demanding management posts is desired. At the same time, municipal manager is expected to develop municipality strategically and possibly bring new ideas and to have good co-operation skills. The management roles that stand out in the job advertisements are entrepreneur, leader, liaison and negotiator. These roles belong to decisional and interpersonal categories. Entrepreneur develops the organisation and leader is the manager of the personnel whereas liaison manages networks. Negotiator represents his/her organisation in different kinds of negotiations. This study shows that municipalities tend to have too narrow perspective in their job advertisements. More attention could be paid to the features and desired personal attributes in the job advertisement. Strong experience in municipal administration and economy refer to abilities to manage municipality effectively and successfully and the meaning of networks and collectiveness is emphasised in the job advertisements. The features of the New Public Management and New Public Leadership can thus be seen in the requirements and management roles of municipal manager.
Keywords: municipal manager; management; management roles; recruitment; fi=Julkisjohtaminen|en=Public Management |; fi=Master's Degree Programme in Intercultural Studies in Communication and Administration|